Religious co-existence in Bangladesh: an empirical study of Hindu perception of Hindu - Muslim relationship in Satkhira - Ushama, Thameem; Obaidullah, Muhammad (2014)
This article presents a case study of the perceptions of Hindus regarding Muslim-Hindu relationship in Bangladesh with special reference to Satkhira district. One view is that as a Muslim majority, Bangladesh maintains peaceful religious coexistence. Another view is quite contrary to it. Despite diversified arguments in the print and electronic Medias, the true state of affair seems to be different with regard to peaceful religious co-existence. This research based on a survey among the Hindus of Satkhira district shows that 89.9% Hindus have congenial relationship with Muslims. 89.4% Hindus attend socio-cultural programmes, i.e. wedding ceremonies, Id festivals and others. 94.3% Hindus take care of the needy regardless of their religious affiliations. 85.1% Hindus cooperate with Muslims in their social life. Obviously, 83.5% Hindus either have business dealings with Muslim partners or prefer to have joint venture with them. 71.2% Hindus assert that Muslims facilitate to enjoy their educational, social, economic, and political rights. 79.4% Hindus have good understanding of each other and strive for peaceful co- existence. 81% Hindus contend that they do not observe religious persecutions and 85.1% record that they live peacefully with their Muslim neighbors. However, 76.5% respondents are of the view that religious conflicts take place due to political differences.